Investigating the Application of TPCK in Javanese Language Learning: The Use of Technology and Instructive Techniques - Subrata, Heru; Hendratno; Zuhdi, Ulhaq (Journal of Education Reseach and Evaluation, 2025)
This study investigates the application of Technological Pedagogical Content Knowledge (TPCK) in the teaching of the Javanese language, focusing on the integration of technology and pedagogical strategies in primary education. The main objective of this research is to evaluate the implementation of TPCK by Javanese language teachers and its impact on teaching practices and student engagement. A quantitative research design was adopted, using a questionnaire distributed to 58 Javanese language teachers in elementary schools. The data were collected using Google Forms and analyzed using descriptive statistical methods. The findings indicate that teachers with a strong understanding of TPCK can effectively integrate technology into their teaching practices, enhancing student interest and motivation in learning the Javanese language. The study identified several effective technological tools, including language learning applications, digital resources related to Javanese culture, and online collaborative learning platforms. However, challenges such as limited technological resources, poor internet connectivity, insufficient teacher training, and overcrowded curricula were found to hinder the full potential of TPCK in Javanese language education. The study contributes significantly to understanding the use of TPCK in Javanese language learning and offers insights for designing more effective teaching materials. The findings may also inform the development of policies and systems that support the use of technology in Javanese language education and beyond.